2020
DOI: 10.3390/nano10091693
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation on Creep Behavior of Nanocrystalline TiAl Alloy

Abstract: TiAl alloy represents a new class of light and heat-resistant materials. In this study, the effect of temperature, pressure, and grain size on the high-temperature creep properties of nanocrystalline TiAl alloy have been studied through the molecular dynamics method. Based on this, the deformation mechanism of the different creep stages, including crystal structure, dislocation, and diffusion, has been explored. It is observed that the high-temperature creep performance of nanocrystalline TiAl alloy is signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Contradicting the claims of Hayes et al [8], the various plots (Figs. [1][2][3][4][5][6], in the present discussion suggest that:…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Contradicting the claims of Hayes et al [8], the various plots (Figs. [1][2][3][4][5][6], in the present discussion suggest that:…”
Section: Discussionsupporting
confidence: 52%
“…A series of reports on room temperature tensile deformation behaviour of γ-TiAl alloys show that the near-γ, two phase compositions having Al contents around 48 at.% possess the highest strengths and ductilities [1]- [3], [11]- [18]. Extensive creep deformation studies have been c arried out on a number of two phase near-γ TiAI alloys produced by various processing routes [8], [19]- [29].…”
Section: Introductionmentioning
confidence: 99%
“…A series of reports on room temperature tensile deformation behaviour of c-TiAl alloys show that the near-c, two phase compositions having Al contents around 48 at.% possess the highest strengths and ductilities [1][2][3][11][12][13][14][15][16][17][18]. Extensive creep deformation studies have been carried out on a number of two phase near-c TiAI alloys produced by various processing routes [8,[19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…
Creep deformation behaviour in single phase c-TiAl alloy has been an extensively studied topic since the late 1970 s. A lot of literatures have reported creep behaviour of c-TiAl alloys, manufactured using different processing techniques [1][2][3][4][5][6][7]. The present discussion revisits the original work on understanding the tensile creep deformation behaviour of wrought single-phase c-TiAl alloy by Hayes et al [8] and is aimed to develop an understanding of steady state creep, through strain vs strain rate and strain vs ln(strain rate) plots.
…”
mentioning
confidence: 99%
“…Further, it has also been reported that the nucleation of dislocation and twinning is often dependent on stacking fault energy in the metals. Molecular dynamics simulations are a well known technique to investigate the atomic mechanisms related to mechanical properties [5][6][7][8][9]36], phase transformation [37,38], deformation behavior [5,6,23,39,40], etc. of both the bulk and nanoscale systems.…”
Section: Introductionmentioning
confidence: 99%